Quantization of Space in the Presence of a Minimal Length*Supported by National Natural Science Foundation of China under Grant Nos. 10865003 and 11464005. (1st June 2015) - Wang, Lun-Zhou; Long, Chao-Yun; Long, Zheng-Wen
Abstract In this article, we apply the Generalized Uncertainty Principle (GUP), which is consistent with quantum gravity theories to an elementary particle in a finite potential well, and study the quantum behavior in this system. The generalized Hamiltonian contains two additional terms, which are proportional to ap3 (the result of the maximum momentum assumption) and α2p4 (the result of the minimum length assumption), where α ∼ 1/MPIc is the GUP parameter. On the basis of the work by Ali et al., we solve the generalized Schrödinger equation which is extended to include the α2 correction term, and find that the length L of the finite potential well must be quantized. Then a generalization to the double-square-well potential is discussed. The result shows that all the measurable lengths especially the distance between the two potential wells are quantized in units of α0lPI in GUP scenario.